Similar Constructive Method for Solving a nonlinearly Spherical Percolation Model - WANG Yong; BAO Xi-tao; LI Shun-chu (Institute of Advanced Engineering and Science, 2013)
In the view of nonlinear spherical percolation problem of dual porosity reservoir, a mathematical model considering three types of outer boundary conditions: closed, constant pressure, infinity was established in this paper. The mathematical model was linearized by substitution of variable and became a boundary value problem of ordinary differential equation in Laplace space by Laplace transformation. It was verified that such boundary value problem with one type of outer boundary had a similar structure of solution. And a new method: Similar Constructive Method was obtained for solving such boundary value problem. By this method, solutions with similar structure in other two outer boundary conditions were obtained. The Similar Constructive Method raises efficiency of solving such percolation model. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2219